2013
DOI: 10.1002/grl.50658
|View full text |Cite
|
Sign up to set email alerts
|

Pore‐scale trapping of supercritical CO2 and the role of grain wettability and shape

Abstract: [1] The capillary trapping of supercritical CO 2 (s-CO 2 ) is postulated to comprise up to 90% of permanently trapped CO 2 injected during geologic sequestration. Successive s-CO 2 / brine flooding experiments under reservoir conditions showed that water-wet rounded beads trapped 15% of injected s-CO 2 both as clusters and as individual ganglia, whereas CO 2 -wet beads trapped only 2% of the injected s-CO 2 as minute pockets in pore constrictions. Angular water-wet grains trapped 20% of the CO 2 but flow was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
138
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(149 citation statements)
references
References 26 publications
11
138
0
Order By: Relevance
“…might be reduced Sarmadivaleh et al, 2015), and a standardised method that does not alter the natural wettability of the quartz is warranted (Saraji et al, 2014;Iglauer et al, 2014). Choudhary et al (2013) have indicated, however, that "[q]uartzrich sandstones are generally water-wet. .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…might be reduced Sarmadivaleh et al, 2015), and a standardised method that does not alter the natural wettability of the quartz is warranted (Saraji et al, 2014;Iglauer et al, 2014). Choudhary et al (2013) have indicated, however, that "[q]uartzrich sandstones are generally water-wet. .…”
Section: Discussionmentioning
confidence: 99%
“…Quartz is often the dominant mineral in sandstone , and many of the units targeted by geosequestration feature quartz as the main component (see Table 3 in Iglauer et al, 2015). The wettability of quartz is of interest because it affects residual capillary trapping, which is one of the main mechanisms for the long-term geological storage of carbon dioxide (Iglauer et al, 2009;Akbarabadi and Piri, 2013) and is most effective in water-wet reservoir materials (Tanino and Blunt, 2012;Iglauer et al, 2012;Choudhary et al, 2013). As a result, the number and scope of studies that have examined wettability -as parameterised by contact angles -of quartz in systems featuring CO 2 and water or brine has grown significantly.…”
Section: Introductionmentioning
confidence: 99%
“…At the pore scale, micro-CT technology has the capability to image the location of the residual phases inside the pore space, thus providing detailed information on the size and shape of the residual ganglia [17][18][19][20][21][22][23][24][25][26][27][28]. Another important application of the micro-CT imaging is the measurement of contact angle at reservoir conditions (elevated temperature and pressure) [29], which is one of the main input parameters for pore-scale numerical modelling.…”
Section: Introductionmentioning
confidence: 99%
“…Because microtomography is non-invasive, it has the ability to study systems at representative conditions, which is particularly attractive for the CO 2 -brine-rock system, as the multiphase flow behavior of scCO 2 is highly dependent on thermo-physical properties, such as interfacial tension and contact angle, which are in turn a strong function of system conditions such as temperature, pressure and salinity [16][17][18] . In such a complex system, with such an extensive and poorly understood set of inter-dependent variables, experiments using idealized pore structures 19 or analogue fluids 20,21 may not be applicable to flow processes in the subsurface. Imaging multiple fluids at conditions representative of a prospective CO 2 injection formation has, however, remained a challenge 22 .…”
Section: Introductionmentioning
confidence: 99%